PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PRODUKTIVITAS PEGAWAI PADA BADAN PUSAT STATISTIK PROVINSI SULAWESI SELATAN - Achsanuddin UA, Anur; Arman, Yuni Kartika (Jurnal Ekonomi Balance, 2016)
This research is done by comprative analysis method. This method is done by comparing the quality of human resources with employee productivity of Central Bureau of Statistics of South Sulawesi Province. The number of research population is 81 employees with the number of samples of 45 employees by using slovin formula with a level of 10%. Data collected by using questionnaire method with Likert scale. Test requirements analysis using R Square test, Test F and Test t. The method of analysis used is simple regression analysis. The results of this study indicate that: (1) there is a positive relationship between the quality of human resources and employee productivity evidenced by the value of R Square (0.216) or equal to 21.6% while the remaining 78.4% influenced by other factors (2) there is a relationship positive between the quality of human resources and employee productivity is evidenced by the value of F (11,865) larger than the table (3.124). (3) there is a positive relationship between the quality of human resources and employee productivity as evidenced by the value of t (3.445) larger than the table (2.037)